Efektivitas Program Komik Bicara Dalam Meningkatkan Pengetahuan dan Sikap Pencegahan Pelecehan Seksual Pada Remaja Tunanetra : Indonesia - adha, Yanuar Laely Lu'luatul; Rahmah, Suqya; Mawardiningih, Eka; Putra, Mohamad Delon Akase; Arifin, Alfin Irfan; Hidayah, Mudita Sri (Jurnal Abdimas Madani dan Lestari (JAMALI), 2026)
The high incidence of sexual violence against visually impaired individuals, particularly in the Special Region of Yogyakarta (26 documented cases), underscores the urgency of providing self-protection education to this vulnerable group. The partner institution, MTs LB/A Yaketunis, faces challenges due to students' minimal understanding of physical interaction boundaries and the lack of adaptive educational media. This community service project aimed to analyze the effectiveness of multisensory media in enhancing the knowledge, attitudes, and protective skills of visually impaired adolescents regarding sexual harassment prevention. The intervention involved the development and implementation of a Braille Comic with Audio Narrative called "Komik Bicara" (Talking Comic). This media covers topics such as body boundaries, gender equality, and simulated assertive responses ('daring to say no'). A Mix Method approach was employed. Program effectiveness was quantitatively measured through pre-test and post-test data, analyzed using the Wilcoxon Signed-Rank Test to determine the significance of improvements in knowledge and attitude scores. Qualitative data from observations and interviews were used to describe the enhancement of students' protective skills. The results demonstrate that the Komik Bicara program successfully and significantly increased student comprehension and skills. This success proves that inclusively designed, multisensory educational media is highly effective in empowering visually impaired adolescents. The project generated the Komik Bicara book and a Teacher Partner Guidebook, which are expected to become permanent references for fostering a safe and disability-friendly school environment.